Conservative Management of Periapical Cementoblastoma: A Case Report - Feli , Mojgan; Taheri , Anita; Raeesi , Pooya; Mashhadi Abbas , Fatemeh; Alam, Mostafa (Iranian Endodontic Journal, 2022)
As a rare ectomesenchymal neoplasm, benign cementoblastoma comprises less than 6% of all odontogenic tumors. The typical treatment plan involves surgical excision and extraction of the affected tooth. Limited evidence, however, suggests the conservative management of this condition as the best treatment. This article discusses the case of a 32-year-old man who had benign cementoblastoma and underwent conservative treatment. The diagnosis was established based on clinical and radiological features analyses. Root canal therapy was performed on the tooth, followed by enucleation, curettage, apicoectomy, and guided bone regeneration (GBR) 30 days later. After a year of follow-up, there was no recurrence, and the tooth was in healthy conditions. These findings demonstrated that the tooth affected by cementoblastoma can be saved. It was treated conservatively to preserve the patient’s oral health and masticatory function.